Improved communication skills of children with Autism Spectrum Disorder using Augmented Reality based on PECS (Picture Exchange Communication System) - Taryadi Taryadi; Ichwan Kurniawan; Sattriedi Wahyu Binabar (Journal of Telematics and Informatics, 2020)
PECS is a method for developing communication using images to exchange desired objects according to the image, especially for children with autism with non-verbal abilities. PECS has many advantages over other communication learning methods that can encourage autistic children to communicate well. Besides having many advantages, the PECS method itself has many disadvantages. The research conducted was to build an application specifically designed for children with autism by correcting the deficiencies that exist in learning with the PECS method. The application is designed with the guidance of an expert Psychologist Children with Special Needs and refers to previous studies as reference material for application interface design. Application testing involves 4 autistic children from 2 different SLBs. Tests are carried out 2 times for each child to find out the progress of application utilization. The test results show that the proposed application is in accordance with the aesthetic design of the MDA framework that is designed so that it is truly able to be accepted by autistic children while also having a positive impact on them, as well as being able to create a learning environment that is more enjoyable both for children with autism and for teachers.